PERILAKU KONSUMSI GENERASI Z PENGGUNA PAYLATER DI KOTA JAMBI: TINJAUAN FAKTOR MOTIVASI DAN GAYA HIDUP - Lara Andela Putri; Addiarrahman; Dessy Anggraini (STKIP Subang, 2026)
The rapid development of digital technology and the increasing use of e-commerce have encouraged the emergence of Paylater services as a practical payment alternative. Generation Z is the most active group using this service due to transaction convenience, promotional offers, and the growth of digital lifestyles. This study aims to analyze the consumption behavior of Generation Z Paylater users in Jambi City from the perspective of motivation and lifestyle factors, as well as identify the characteristics of their consumption behavior. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, literature reviews, and documentation. Informants were selected using purposive sampling techniques consisting of Generation Z individuals actively using Paylater services. The findings reveal that Paylater usage is influenced by both utilitarian and hedonic motivations. Utilitarian motivation arises because Paylater helps users fulfill urgent needs and manage cash flow, while hedonic motivation is driven by instant gratification, social trends, and social media influence. The consumption behavior of Generation Z Paylater users is characterized by high transaction frequency, dominance of purchases in fashion, skincare, gadgets, and entertainment products, as well as dependence on promotions and cashback offers. From the perspective of Islamic economics, the use of Paylater has the potential to encourage excessive consumption behavior (israf) and raise concerns regarding elements of usury (riba) if not accompanied by adequate financial literacy.